Divine misdemeanors a novel - Hamilton, Laurell K (New York Ballantine Books, 2009)
Someone is killing the fey, which has left the LAPD baffled and Merry Gentry, Los Angeles private eye and princess of faerie, determined to get to the bottom of the case even if means going up against Gilda, the Fairy Godmother. But even stranger things are happening. Mortals Gentry once healed with magic are suddenly performing miracles, a shocking phenomenon wreaking havoc on human/faerie relations
1
Keywords: Fairies -- Fiction; Gentry, Meredith (Fictitious character) -- Fiction; Paranormal fiction; Women private investigators -- Fiction; Fantasy fiction; Mystery fiction